Hubungan Minat Mengikuti Ekstrakurikuler Pendidikan Kepramukaan dengan Kedisiplinan Anggota Gudep di Gugus X Kota Bengkulu - Eri Candramustika; Lukman Lukman; Osa Juarsa (Universitas Bengkulu, 2019)
The purpose of this research is to analyze the relationship between extracurricular interests follow Scouting education with discipline a member Gudep found in Bengkulu City cluster of X. The quantitative approach used and the type of research that used korelasional. The population in this research is the entire members of the Gudep contained in the cluster X 332 by the amount of Bengkulu City students. The sample in this research totalled 84 students. Sampling techniques in the research of this proportionate stratified random sampling. Instrument in this study is the sheet now. Data collection techniques using question form. Data analysis techniques using test prerequisites and test hypotheses using the correlation formula product moment. The results of this research show that the value of rxy = 0.695 with rtabel = 0.212 (0.695 > 0.212), KP = 48.3%, and thitung = 5.74, with ttabel = 1.663 (5.74 > 1.663). Thus, it can be concluded that there is a significant relationship between interest in extracurricular education follow Scouting with the discipline of members in Gudep cluster X city of Bengkulu.